PHASE CHANGES ON 4H AND 6H SIC AT HIGH TEMPERATURE OXIDATION - Setiawan, Jan; Suryaman, Ganisa Kurniati; Masrukan (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The oxidation on two silicon carbide contains 6H phase and contains 6H and 4H phases has been done. Silicon carbide is ceramic non-oxide with excellent properties that potentially used in industry. Silicon carbide is used in nuclear industry as structure material that developed as light water reactor (LWR) fuel cladding and as a coating layer in the high temperature gas-cooled reactor (HTGR) fuel. In this study silicon carbide oxidation simulation take place in case the accident in primary cooling pipe is ruptured. Sample silicon carbide made of powder that pressed into pellet with diameter 12.7 mm and thickness 1.0 mm, then oxidized at temperature 1000 oC, 1200 oC dan 1400 oC for 1 hour. The samples were weighted before and after oxidized. X-ray diffraction con-ducted to the samples using Panalytical Empyrean diffractometer with Cu as X-ray source. Diffraction pattern analysis has been done using General Structure Analysis System (GSAS) software. This software was resulting the lattice parameter changes and content of SiC phases. The result showed all of the oxidation samples undergoes weight gain. The 6S samples showed the highest weight change at oxidation temperature 1200 oC, for the 46S samples showed increasing tendency with the oxidation temperature. X-ray diffraction pattern analysis showed the 6S samples contain dominant phase 6H-SiC that matched to ICSD 98-001-5325 card. Diffraction pattern on 6S showed lattice parameter, composition and crystallite size changes. Lattice parameters changes had smaller tendency from the model and before oxidation. However, the lowest silicon carbide composition or the highest converted into other phases up to 66.85 %, occurred at oxidation temperature 1200 oC. The 46S samples contains two polytypes silicon car-bide. The 6H-SiC phases matched by ICSD 98-016-4972 card and 4H-SiC phase matched by ICSD 98-016-4971 card. Diffraction pattern on 46S also showed lattice parameter, composition and crystallite size changes. The lattice parameter changes not significant. For 6S and 46S samples at 1400 oC, the 6H-SiC phase changes into other phases more than 50 % from its original weight percentage.